Effect of Virgin Coconut Oil on Skin Integrity in The Elderly with Incontinence - Sukhri Herianto Ritonga; Nanda Masraini Daulay (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Intorduction:Incontinence was a problem that often occurs in the elderly and this condition can worsen the elderly situation with the appearance of severe damage to the integrity of the skin,Virgin Coconut Oil (VCO) contains medium chain saturated fat that easily enters deep skin layers and maintains skin elasticity and suppleness. The aim of this study was to determine the effect of virgin coconut oil on skin integrity in the elderly with incontinence.Methods: The design of research was a quasi-experimental with non equivalent control group design. The population in this study were all elderly who experience incontinence. The sampling technique used was consecutive sampling with a total of 10 people in the experimental group and 10 people in the control group. To assess skin integrity before and after treatment is used was The Ghent Global IAD (GLOBIAD) tool. The using of virgin coconut oil is done every time after the stool incontinence episode and after bathing. Virgin coconut oil has been applied to the damaged skin and also to other vulnerable skin. Results: Based on the Wilcoxon test results obtained p value smaller than 0.05 which is 0.010 so that there was a significant difference in the value of skin integrity before and after the treatment. Conclusions:There was a significant effect on the use of virgin coconut oil on skin integrity in the elderly with incontinence.